History of the Caspian mollusks of Didacna genus in the Black Sea - T. A. Yanina (Юг России: экология, развитие)
On the base of the vast factual evidences and mollusk-collections, gathered by author during multiyear investigations in the Black Sea and Caspian regions, the questions on taxonomical composition, age of invasion and expansion of the Caspian mollusks of Didacna genus in the Black Sea’ Pleistocene basins are considered in the article.